Tecnologias, currículo e práticas de uma escola de ensino fundamental em Uruaçu - GO: uma análise crítica das competências digitais - (:unkn) unknown (Universidade Estadual de Goiás, 2026)
This study, linked to the Education, School and Technologies research line of the Interdisciplinary Graduate Program in Education,Language and Technologies at the State University of Goiás (PPGIELT-UEG), aims to analyze the incorporation of digital technologies in the school context, as well as the curricular guidelines that orient them, examining their materialization in the pedagogical practices of teachers in a municipal public school. The research is guided by the following question: what are the perceptions of teachers in a public school regarding the incorporation of technology established in official curricular frameworks, considering the social, institutional and formative conditions that shape their professional daily life? This qualitative, exploratory study was conducted in a municipal school in Uruaçu, Goiás, involving classes from the 1st to the 5th grade of Elementary Education and their respective teachers. Data collection included questionnaires, interviews and document analysis, organized according to Content Analysis as proposed by Bardin (2016). The understanding of digital competence developed in this study dialogues with the definition proposed by Ferrari (2012), without assuming full agreement with its assumptions, given the historical origins of the term “competence” associated with the demands of the capitalist system. The critical discussion on technology and society is grounded in Feenberg’s (2010) philosophy of technology, which conceives technology as a historical and cultural construction whose rationality requires ethical, political and social problematization. The results indicate that the use of digital technologies in school practices remains restricted to an operational function, mainly as support resources for classroom activities, limiting their potential to reorganize relations between teachers, students and knowledge. Although digital competencies occupy a central place in curricular documents, their integration into pedagogical practices occurs in a punctual manner, constrained by precarious technological infrastructure and superficial training processes. In this context, digital technologies tend to operate under an ideological logic, being presented as technical solutions to complex educational challenges. It is concluded that the curriculum, constituted on capitalist and neoliberal bases, assumes an instrumental character and conditions the incorporation of digital technologies into pedagogical practices, requiring infrastructure, teacher education policies and critical approaches that prevent their utilitarian reduction
Technologies, curriculum, and practices in a public elementary school in Uruaçu, Goiás: a critical analysis of digital competencies
Keywords: tecnologias digitais - currículo - ideologia; tecnologias digitais - formação docente; tecnologias digitais - práticas pedagógicas; digital technologies - curriculum - ideology; digital technologies - teacher education; digital technologies - pedagogical practices; CIENCIAS HUMANAS::EDUCACAO